Pengetahuan Fraktur dan Pembidaian Perawat Aceh Tengah (IJM: Journal of Multidisiplinary, 2025)
Fracture is an emergency condition that requires rapid and appropriate first aid at the scene. Fracture cases are generally caused by injuries resulting from traffic accidents, falls, or trauma due to sharp or blunt objects. One form of first aid for fractures is splinting, which serves to immobilize the fractured or injured bone to prevent further complications. This study aims to identify the level of knowledge among nurses in Central Aceh regarding fractures and splinting. This research is a descriptive study with a cross-sectional design. The study population consisted of nurses from four public health centers (puskesmas) in Central Aceh, with a total sample of 60 respondents selected using a total sampling technique and data collected through questionnaires. The results showed that all nurses (100%) had a good level of knowledge about fractures, while knowledge about splinting indicated that 40 respondents (67%) had good knowledge and 20 respondents (33%) had moderate knowledge. It is expected that the findings of this study can serve as a basis for nurses to further enhance their knowledge and skills in managing fracture patients and performing proper splinting procedures.